2020
DOI: 10.1016/j.resourpol.2020.101856
|View full text |Cite
|
Sign up to set email alerts
|

The predictive power of oil price shocks on realized volatility of oil: A note

Abstract: This paper examines the predictive power of oil supply, demand and risk shocks over the realized volatility of intraday oil returns. Utilizing the heterogeneous autoregressive realized volatility (HAR-RV) framework, we show that all shock terms on their own, and particularly financial market driven risk shocks, significantly improve the forecasting performance of the benchmark HAR-RV model, both in- and out-of-sample. Incorporating all three shocks simultaneously in the HAR-RV model yields the largest forecast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 48 publications
0
18
0
1
Order By: Relevance
“…They suggested that policymakers and investors should consider volatility shocks through various swaps to construct a favorable hedging strategy decision toward market risk. Additionally, Demirer et al (2020) analyzed the forecasting power of oil demand, the oil supply, and risk-driven shocks across the realized volatility for high-frequency data. Thus, the authors used a Heterogeneous Autoregressive Realized Volatility (HAR-RV) approach introduced by Corsi (2009) and the framework established by Ready (2018) to fragment oil price shocks into three shock components: oil demand shocks, oil supply shocks, and risk shocks related to financial market risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that policymakers and investors should consider volatility shocks through various swaps to construct a favorable hedging strategy decision toward market risk. Additionally, Demirer et al (2020) analyzed the forecasting power of oil demand, the oil supply, and risk-driven shocks across the realized volatility for high-frequency data. Thus, the authors used a Heterogeneous Autoregressive Realized Volatility (HAR-RV) approach introduced by Corsi (2009) and the framework established by Ready (2018) to fragment oil price shocks into three shock components: oil demand shocks, oil supply shocks, and risk shocks related to financial market risk.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that all shock components, on their own, significantly produce extended forecasting completion of the HAR-RV process. Furthermore, Demirer et al (2020) provided crucial information for investors and market agents when controlling for oil market volatility. Other recent researchers have also examined the forecasting structure of the realized volatility for oil price returns by implementing the HAR-RV approach ( Prokopczuk et al, 2016 ; Degiannakis and Filis, 2017 ; Wen et al, 2019 ; Liu et al, 2018 ; Chen et al, 2019 ; Yang et al, 2019 ; Bonato et al, 2020 ; and Gkillas et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly (Narayan, 2020) documented that COVID-19 infections have a significant impact on volatility and returns in oil market. Further, (Demirer et al, 2020) reported that significant predictive information over volatility of oil market is apprehended by shocks in financial risk even after supply and demand shocks in the market are taken as control variables. The result of this study also suggested that a discrete channel of risk transmission exists between commodity and financial markets.…”
Section: Introductionmentioning
confidence: 99%
“…Trade in fuels, on the contrary, has been severely affected by the pandemic, while oil prices have turned out to be far more perceptible to the slowdown of economic activities compared to mineral prices [138][139][140]. Global oil demand has been depressed with restrictions on travel and transport and industrial activity cuts across the world [1].…”
Section: Market Effectsmentioning
confidence: 99%